THE POWER OF SPOKEN WORDS: UNRAVELING THE CONNECTION BETWEEN VERBAL COMMUNICATION AND PUBLIC RELATIONS - Tan, Julia (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
Effective verbal communication skills play a crucial role in contemporary social environments, fostering interpersonal interactions and facilitating the functioning of society. Public relations, characterized by its unique role in social regulation, demonstrates specificity, subsidiarity, and facilitation as it evolves. Central to this evolution is the interaction and cooperation between organizations and the public, with communication and exchange serving as pivotal avenues for public relations activities. Leveraging these communication channels allows for the comprehensive transmission of vital information and data, ultimately establishing relationships founded on trust and understanding [1]. Given its significance as a communication form in the ongoing development of our society, public relations, with its inherent communication skills and capabilities, warrants in-depth consideration. To this end, it is imperative that we thoroughly examine the forms and techniques of verbal communication within the context of public relations. Such scrutiny is essential for mitigating communication challenges and ensuring the seamless functioning of public relations.